Antibacterial activity assessment of eyeliner extracted from natural sources (castor oil & sandalwood) - T. APARNA; N. JYOTHI; M. KEZIA ELIZABETH; D.S.N. PRAVEENA; K. SWETHA; S. SHAILAJA (International Journal of Pharma and Bio Sciences, 2017)
Our nature is a valuable source of various valuable compounds, which can be used in treatment of some diseases and to enhance our beauty. Traditionally natural products extracted from plants were used to make many cosmetics, one such product is eyeliner (used in present study). The natural eyeliner was extracted from Castor oil, Sandalwood and Bronze metal by traditional method. The crude extract was dissolved in standard solvents like ethanol and its antibacterial activity of crude extract was evaluated against bacterial cultures of Staphylococcus, E.coli, Klebsiella. Simultaneously, the antibacterial activity of even the commercial eyeliner was evaluated against the bacterial cultures staphylococcus, E.coli, Klebsiella. The inhibitory activity of natural eyeliner and commercial eyeliner were compared. The focus of present study lies in the investigation of antimicrobial activity of the naturally extracted crude eyeliner and commercial eyeliner. From the analysis it was found that crude extract of natural eyeliner is more effective against the bacterial test Organisms. The staphylococcus species was found to be more susceptible among the bacterial cultures tested. The crude extract of natural eyeliner containing castor oil, Sandalwood and metal bronze was found to be antibacterial. The common eye infections are caused by Staphylococcus and it was found that our natural product is showing antibacterial activity against the organism Staphylococcus. The Zone of inhibition was evaluated and the crude extract was found to be more effective against Staphylococcus as compared to commercial eyeliner. The outcome of the present study reveals that the natural eyeliner is found to be more antibacterial than the commercial eyeliner and useful effects of natural products.